Mapping Sound Pressure Levels: A Novel Approach to Determining Near-field and Far-field Regions - ILIEV, Iliyan Yordanov; KARAIVANOV, Hristo Zhivomirov (Archives of Acoustics, 2025)
The present study focuses on the spatial characteristics of the sound pressure level (SPL) generated by a circular piston (a circular-shaped acoustic transducer or loudspeaker). It presents a short theoretical review to aid in understanding the primary sound field characteristic – acoustic pressure – as a function of time, frequency, directivity angle, and distance from the source. The study introduces a simple and practical criterion for determining the near- and far-field boundary along the axis of the circular piston as a function of frequency. This criterion is validated through theoretical analysis and experimental measurements. Overall, the results show the influence of circular piston parameters on the SPL spatial distribution.